Captive Birth of Tiger Shark (Galeocerdo cuvier) Reveals a Shift in Respiratory Mode during Parturition - Tomita, Taketeru; Touma, Hideyuki; Murakumo, Kiyomi; Yanagisawa, Makio; Yano, Nagisa; Oka, Shin-ichiro; Miyamoto, Kei; Hanahara, Nozomi; Sato, Keiichi (Copeia, 2018)
Ram ventilation, which is characterized by the production of a respiratory water current over the gill by locomotory effort, widely occurs among pelagic sharks. However, the process by which the juvenile starts this respiratory mechanism remains largely unknown. The captive birth of a Tiger Shark (Galeocerdo cuvier) at the Okinawa Churaumi Aquarium on 23 March 2017 permitted the examination of the parturition process and behavior of newborn juveniles of this species. Sonographic examination of the pregnant female showed that, unlike adult Tiger Sharks, embryos used buccal pumping, revealing that Tiger Shark shifts its respiratory mechanism from buccal pumping to ram ventilation after birth. Our observation also showed that ram ventilation of the neonate was not continuous, and buccal pumping was also used when the neonate intermittently rested on the bottom of the tank. We speculate that this behavior is the transitional phase in the shift from buccal pumping to ram ventilation in neonates, and continuous ram ventilation may be established after the development of continuous and fast swimming abilities.